2015
DOI: 10.1159/000398815
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hemodynamic Response to Exercise in Chronic Thromboembolic Pulmonary Hypertension before and after Pulmonary Endarterectomy

Abstract: put (CO) from 4.4 ± 0.8 to 6.5 ± 1.9 l/min and diastolic pulmonary gradient (DPG) from 14.6 ± 4.9 to 20.7 ± 12.7 mm Hg. Post-PEA mPAP increased from 23.7 ± 6.6 at rest to 43.2 ± 7.1 mm Hg, while CO increased to a higher extent from 5.1 ± 0.9 to 8.4 ± 1.9 l/min. There were significant correlations between pre-PEA DPG/CO and dPAP/CO slopes with the pulmonary vascular resistance (Spearman r = 0.578, p = 0.019, and r = 0.547, p = 0.028) and mPAP at rest after PEA (Spearman r = 0.581, p = 0.018, and r = 0.546, p = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 47 publications
(68 reference statements)
2
15
0
Order By: Relevance
“…Previous studies have shown that clinical functional status assessed with NYHA classification or direct assessment of exercise tolerance by 6‐minute walk test or VO 2 improves significantly after PEA . In accordance with these previous findings, we demonstrated significant improvement in exercise capacity as maximal oxygen consumption increased significantly during follow‐up.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Previous studies have shown that clinical functional status assessed with NYHA classification or direct assessment of exercise tolerance by 6‐minute walk test or VO 2 improves significantly after PEA . In accordance with these previous findings, we demonstrated significant improvement in exercise capacity as maximal oxygen consumption increased significantly during follow‐up.…”
Section: Discussionsupporting
confidence: 91%
“…After PEA, the afterload decreases, leading to increase in RV free- 3,11,12,35 In accordance with these previous findings, we demonstrated significant improvement in exercise capacity as maximal oxygen consumption increased significantly during follow-up.…”
Section: Rv Function By Stress Echocardiography and Physical Capacitysupporting
confidence: 91%
See 2 more Smart Citations
“…Building on this concept, an increase in the ratio of change in mPAP to change in CO between rest and exercise (mPAP-CO slope) greater than 3 mm Hg/L/min was shown to associate with further limitations in peak V : O 2 and ventilation in patients with interstitial lung disease (10). Another study found that the 6-minute-walk distance (6-MWD), when combined with echocardiography, could provide a noninvasive estimate of TPR and that an mPAP-CO slope greater than 3.3 mm Hg/L/min was predictive of developing PAH (11), while alterations in the mPAP-CO slope correlate with hemodynamic improvement 1 year after pulmonary endarterectomy or after medical therapy with sildenafil for the treatment of chronic thromboembolic pulmonary hypertension (CTEPH) (12,13).…”
Section: Rv-pulmonary Arterial Couplingmentioning
confidence: 99%